Developing A Prediction Tool To Improve The Shading Efficiency Of The Pedestrian Zones - Khudhayer, Wael A. (2020)
Since the last quarter of the twentieth century, the rapid growth in many cities throughout the world was the predominant cause of the phenomenon of urban sprawl. In this backdrop, The over-expanded urban spaces let to intensify the negative impact of the high solar radiation in the hot climate regions that caused abandoned pedestrian zones. There is a growing body of literature highlighted the compacted urban spaces as the most prioritized approach against urban sprawl and high solar radiation. The compacted pedestrian zones reduce the overexpansion and mitigate solar radiation by promoting mutual shading. Meanwhile, controlling the morphology of the pedestrian zone have been identified as an essential contributing factor to improve shading and limitate the overexpansion. The morphology of the pedestrian zone was described by three parameters proportions, orientation, and vegetation. These descriptors are characterized by being variable within the urban fabric, resulting in a difference in the shading efficiency in the pedestrian zones. Besides, the shading requirements toward pedestrian also vary since the shading is a dynamic physical phenomenon that changes in daily and seasonally basis to a specific geographic location. Hence, the variability of the morphology descriptors and shading requirements have made controlling the over-expansion in the pedestrian zone a complicated issue. Therefore, the majority of the studies have utilized computer simulation using different shading assessment software and tools. Although the shading can be calculated using these software and tools at a high level of accuracy; however, they are considered as an analytical tool. The available software and shading assessment tools did not provide regulatory constraints to control the overexpansion pedestrian zone to an effective limit that keeps shading feasible for the pedestrian. Hence, there is an uncertainty of providing a tangible policy to improve shading in the pedestrian zones. Consequently, in this study, a prediction tool was developed to set regulatory constraints by identifying the expansion limit corresponding to the targeted shading efficiency. The shading efficiency represented the percentage of the shaded area to the total floor area of the pedestrian zone, while the targeted shading efficiency indicated the preferable shading requirements for the pedestrian. The development of the prediction tool was conducted base on integrating three sequenced algorithms, which are sun position algorithm, shadow length and position algorithm, and expansion limit algorithm. Then the developed prediction tool was tested in the Muscat coordinates. The study concluded that the shading performance in the pedestrian zone was due to a combination of effective morphology configuration within a particular expansion limit. Moreover, the study provided systematic solutions based on reconfiguring the pedestrian zone by the trees. The trees can behave as an environmental modifier to maintain the shading of the pedestrian zone within an acceptable level. Then ECOTECT software has utilized to validate the effectiveness of the developed prediction tool for evaluating and improving the shading efficiency in the pedestrian zone. The ECOTECT has been selected because of its capabilities that allow the user to simulate and compare the shadow casting ability for both unshaded and shaded scenarios. The results of ECOTECT simulation validated the effectiveness of the prediction tool to provide regulatory constraints to evaluate and improve the shading efficiency of the pedestrian zone.